Pengujian Starter Yoghurt (Streptococcus thermophilus dan Lactobacillus bulgaricus) serta Ekstrak Jamblang (Syzygium cumini L.) Pada Kasus Niyoghurt Jamblang Yang Telah Rusak - Sarah Sarah; Eti Indarti; Dewi Yunita (Jurnal Ilmiah Mahasiswa Pertanian, 2021)
Abstract. Yogurt with the use of coconut milk as raw material is known as niyogurt or cocogurt. Coconut milk can be used as a base for yogurt because it has the same fat content as milk in terms of color and thickness similar to full cream milk. Preliminary research to breed starter Streptococcus thermophilus and Lactobacillus bulgaricus on coconut milk media with the addition of milk gradually. The results of the preliminary study showed that the pH value of the Streptococcus thermophilus and Lactobacillus bulgaricus cultures slightly increased at the use of 40% coconut milk and decreased until the use of 80%. However, when using 100% coconut milk, the pH of the two starters increased again. In the main study, making yoghurt with variations in the percentage of starter (3% (S1), 4% (S2) and 5% (S3)) and the percentage of jamblang fruit extract (Syzygium cumini L.) (10% (J1), 20% (J2) and 30% (J3)). The main research results show that the yoghurt has been damaged which is characterized by a rancid aroma, does not have a sour taste, and gas bubbles appear. The pH of niyoghurt ranges from 5.0-5.38 with an average of 5.19. This value is not in accordance with the SNI for yoghurt (01-2981-1992).(Examining of yogurt starter (Streptococcus thermophilus and Lactobacillus bulgaricus) and Syzygium cumini L. Extract in the Case of Spoilt Fruit Niyoghurt)Abstract. Yogurt with the use of coconut milk as raw material is known as niyogurt or cocogurt. Coconut milk can be used as a base for yogurt because it has the same fat content as milk in terms of color and thickness similar to full cream milk. Preliminary research to breed starter Streptococcus thermophilus and Lactobacillus bulgaricus on coconut milk media with the addition of milk gradually. The results of milk gradually. The results of preliminary research showed the pH value of the Biaken Streptococcus thermophilus and Lactobacillus the use of 40% coconut milk and deceased to 80% use. However, when using 100% coconut milk, the pH of the two starters increased again. In the main study, making yogurt with variations in the percentage of starter (3% (S1), 4% (S2) and 5% (S3%)) and the percentagee of jamblang fruit extract (Syzygium cumini L.) (10%(J1), 20%(J2) and 30% (J3)). The main research results show that the yogurt has been demaged which is characterized by a rancid aroma, does not have a sour taste, and gas bubbles appear. Acording to SNI for yogurt (01-2981-1992)